The Routledge companion to women and monarchy in the ancient Mediterranean world
1 online resource
Keywords: "This volume offers the first comprehensive look at the role of women in the monarchies of the ancient Mediterranean. It consistently addresses certain issues across all dynasties: title, role in succession, the situation of mothers, wives and daughters of kings, regnant and co-regnant women, role in cult and in dynastic image, while also examining a sampling of the careers of individual women while placing them within broader contexts. Written by an international group of experts, this collection is based on the assumption that women played a fundamental role in ancient monarchy, that they were part, not apart from it, and that it is necessary to understand their role to understand ancient monarchies. This is a crucial resource for anyone interested in the role of women in antiquity"--